Wiley 2022 interpretation and application of IFRS standards - Alibhai, Salim (Wiley Regulatory Reporting, 2022)
The 2022 reference for the interpretation and application of the latest international financial reporting standards, this book is a revised and comprehensive resource that includes the information needed to interpret and apply International Financial Reporting Standards (IFRS®) as outlined by the International Accounting Standards Board (IASB). This resource contains a wide range of practical examples as well as invaluable guidance on the expanding framework for unified financial reporting. The authors provide IFRIC interpretations and directions designed to ensure a clear understanding of the standards. The IFRS® standards are ever evolving - therefore, it is essential that professionals and students have the information needed to apply the standards correctly in real-world cases. This volume offers a complete, up-to-date reference that aids in the application of the latest international standards in a manner that is transparent, accountable, and efficient. This edition includes IFRS 17 Insurance Contracts which has an effective date of 1 January 2023. This guide is written by PKF professionals who support the application of clear, informative, and accurate financial reporting. PKF International member firms specialise in providing high quality audit, accounting, tax, and business advisory solutions to international and domestic organisations around the globe. PKF International is a member of the Forum of Firms - an organisation dedicated to consistent and high-quality standards of financial reporting and auditing practices worldwide. PKF International Limited administers a family of legally independent firms and does not accept any responsibility or liability for the actions or inactions of any individual member or correspondent firm or firms.